2023
DOI: 10.1126/science.ade5671
|View full text |Cite
|
Sign up to set email alerts
|

Female preference for rare males is maintained by indirect selection in Trinidadian guppies

Abstract: When females prefer mates with rare phenotypes, sexual selection can maintain rather than deplete genetic variation. However, there is no consensus on why this widespread and frequently observed preference might evolve and persist. We examine the fitness consequences of female preference for rare male color patterns in a natural population of Trinidadian guppies, using a pedigree that spans 10 generations. We demonstrate (i) a rare male reproductive advantage, (ii) that females that mate with rare males gain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The remarkable variation in male guppy coloration has made them a model for studies of female preference ( 2 , 3 ) and the interaction of sexual and natural selection ( 4 , 27 ). Male patterns in many populations have been shown to exhibit strong patterns of Y-linkage ( 8 , 14 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remarkable variation in male guppy coloration has made them a model for studies of female preference ( 2 , 3 ) and the interaction of sexual and natural selection ( 4 , 27 ). Male patterns in many populations have been shown to exhibit strong patterns of Y-linkage ( 8 , 14 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Male guppies, Poecilia reticulata , exhibit remarkable variation in coloration, which has been extensively studied in the context of fitness ( 1 ) and female preference ( 2 , 3 ). The widespread variation in the extent and patterning of male color across wild populations ( 4 , 5 ) and the rapid response to changes in natural and artificial selection ( 6 , 7 ), coupled with high heritability estimates ( 8 , 9 ) all suggest that substantial genetic variation for this trait is maintained in guppy populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reid et al (2005), using pedigrees covering 20 years, found that male song-sparrow (Melospiza melodia) song repertoire predicts the number of grandoffspring, although in this species paternal care makes it difficult to separate paternal effects (direct benefits) and genetic effects. Recent study on guppies showed that females that mated with rare males had increased number of grandoffspring (Potter et al, 2023).…”
mentioning
confidence: 99%
“…reproductive success Elgee et al, 2012;Herdegen-Radwan, 2019; maturation time, juvenile survival, female fecundity Herdegen-Radwan, Cattelan et al, 2021), to negative effects (juvenile survival Brooks, 2000;sperm quality Evans, 2010). However, apart from one recent study looking at the effect of colour pattern frequency on fitness (Potter et al, 2023), no other studies have tested for the association between epigamic traits of male guppies and a fitness measure as comprehensive and integrative as number of grandoffspring.…”
mentioning
confidence: 99%